Establishment of AA-NAT, SCD, PROP1, and IGFBP3 gene frequency distributions in Karacabey Merino and Kivircik Sheep Breeds - Dinçel, D; Çobanoğlu, Ö (Journal of the Hellenic Veterinary Medical Society, 2023)
Thus, the aim of the current study was to investigate the genotypic dispersion of AA-NAT, SCD, PROP1, and IGFBP3 genes in the target population. Primarily, the genomic DNA was isolated from blood samples by the phenol/chloroform method. The genomic analyses were performed on a total of 160 Karacabey Merino (KM) sheep (n=80) and Kivircik (n=80). The PCR-RFLP method was used to determine the genotype of the SNPs. Deviation from Hardy–Weinberg equilibrium (HWE) and population genetic assays such as observed (Ho) and expected (He) heterozygosities, effective allele numbers (Ne), and the polymorphism information content (PIC) were calculated for each gene in the population. As a result, there was no deviation from HWE was determined except SCD and PROP1 gene in KM. The most frequent genotypes were found AA (66,25% and 87,50%) for AA-NAT gene, CC (93,75% and 91,25%) for SCD gene and CC genotype (70,00% and 56,25%) for PROP1 gene in KM and Kivircik sheep. All breeds were detected monomorphic in terms of the IGFBP3 gene. In conclusion, the other regions of the IGFBP3 gene which were determined as monomorphic in the studied flock could be researched. Moreover, further studies should be necessary for defining the effects of investigated genes on related traits in KM and Kivircik sheep in terms of polymorphic genes specified.